A novel Zn2Cys6 transcription factor BcGaaR regulates D‐galacturonic acid utilization in Botrytis cinerea. Issue 2 (19th January 2016) - Zhang, Lisha; Lubbers, Ronnie J.M.; Simon, Adeline; Stassen, Joost H.M.; Vargas Ribera, Pablo R.; Viaud, Muriel; van Kan, Jan A.L.
Summary: D‐galacturonic acid (GalA) is the most abundant monosaccharide component of pectin. Previous transcriptome analysis in the plant pathogenic fungus Botrytis cinerea identified eight GalA‐inducible genes involved in pectin decomposition, GalA transport and utilization. Co‐expression of these genes indicates that a specific regulatory mechanism occurs in B. cinerea . In this study, promoter regions of these genes were analysed and eight conserved sequence motifs identified. The Bclga 1 promoter, containing all these motifs, was functionally analysed and the motif designated GalA Responsive Element (GARE) was identified as the crucial cis ‐regulatory element in regulation of GalA utilization in B. cinerea . Yeast one‐hybrid screening with the GARE motif led to identification of a novel Zn2 Cys6 transcription factor (TF), designated BcGaaR. Targeted knockout analysis revealed that BcGaaR is required for induction of GalA‐inducible genes and growth of B. cinerea on GalA. A BcGaaR‐GFP fusion protein was predominantly localized in nuclei in mycelium grown in GalA. Fluorescence in nuclei was much stronger in mycelium grown in GalA, as compared to fructose and glucose. This study provides the first report of a GalA‐specific TF in filamentous fungi. Orthologs of BcGaaR are present in other ascomycete fungi that are able to utilize GalA, including Aspergillus spp., Trichoderma reesei and Neurospora crassa . Short Abstract: The transcriptional regulator that controls D‐galacturonic acid (GalA) utilization in fungi was unknown. We identified in Botrytis cinerea a novel Zn2 Cys6 transcription factor (TF), designated BcGaaR, which is required for the induction of GalA‐utilization genes. The BcGaaR protein was predominantly localized in nuclei in cultures grown on GalA, but remained in the cytoplasm in cultures grown on glucose. This study provides the first report of a GalA‐specific TF in filamentous fungi. Orthologs of BcGaaR are present in other ascomycete fungi.